If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 = 4 + q Solving 61 = 4 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. 61 + -1q = 4 + q + -1q Combine like terms: q + -1q = 0 61 + -1q = 4 + 0 61 + -1q = 4 Add '-61' to each side of the equation. 61 + -61 + -1q = 4 + -61 Combine like terms: 61 + -61 = 0 0 + -1q = 4 + -61 -1q = 4 + -61 Combine like terms: 4 + -61 = -57 -1q = -57 Divide each side by '-1'. q = 57 Simplifying q = 57
| 7x^2+28x+196=0 | | -5(t-1)+t=5t-9 | | 5x^2+45x+70= | | x*2-6x-4=0 | | X(2x-5)+(3x+4)(6x-1)= | | 3x^2+42x+441=0 | | 73x-15=48+99 | | x+(x*.04)=2.75 | | (x+0.2)(x+3.9)=0 | | 28d+1=28 | | x^2+4x+28=0 | | x+x(.04)=2.75 | | 3(7-2h)=9 | | x^2=y-1 | | -s+3=52+21 | | x^2+34x+2= | | -x^2+565x-8250=0 | | (x-y)(x^2-10xy+y^2)=0 | | b-[x+4a+(x-7)]= | | 9+4+4v-2v+6=11 | | 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) | | 144=4q+4q | | 4x-3=3(-1+x) | | x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 |